Prevention of bleomycin‐induced lung fibrosis via inhibition of the MRTF/SRF transcription pathway - Kendell M. Pawelec; Megan Varnum; Jack R. Harkema; Bruce Auerbach; Scott D. Larsen; Richard R. Neubig (Wiley, 2022)
Abstract Bleomycin‐induced lung fibrosis is a debilitating disease, linked to high morbidity and mortality in chemotherapy patients. The MRTF/SRF transcription pathway has been proposed as a potential therapeutic target, as it is critical for myofibroblast differentiation, a hallmark of fibrosis. In human lung fibroblasts, the MRTF/SRF pathway inhibitor, CCG‐257081, effectively decreased mRNA levels of downstream genes: smooth muscle actin and connective tissue growth factor, with IC50s of 4 and 15 μM, respectively. The ability of CCG‐257081 to prevent inflammation and fibrosis, measured via pulmonary collagen content and histopathology, was tested in a murine model of bleomycin‐induced lung fibrosis. Animals were given intraperitoneal bleomycin for 4 weeks and concurrently dosed with CCG‐257081 (0, 10, 30, and 100 mg/kg PO), a clinical anti‐fibrotic (nintedanib) or the clinical standard of care (prednisolone). Mice treated with 100 mg/kg CCG‐257081 gained weight vs. vehicle‐treated control mice, while those receiving nintedanib and prednisolone lost significant weight. Hydroxyproline content and histological findings in tissue of animals on 100 mg/kg CCG‐257081 were not significantly different from naive tissue, indicating successful prevention. Measures of tissue fibrosis were comparable between CCG‐257081 and nintedanib, but only the MRTF/SRF inhibitor decreased plasminogen activator inhibitor‐1 (PAI‐1), a marker linked to fibrosis, in bronchoalveolar lavage fluid. In contrast, prednisolone led to marked increases in lung fibrosis by all metrics. This study demonstrates the potential use of MRTF/SRF inhibitors to prevent bleomycin‐induced lung fibrosis in a clinically relevant model of the disease.